Supervision Strategy of the Head of Service to Achieve Effective Work of Bapenda Employees of Majalengka Regency (Innovation of Supervision Strategy of MOM and DAD Championship) - Nirwana, Anggita Puspa; Denissa Angela Sihombing; Shilvy Rizky Ramadita; Ivan Darmawan (Indonesian Journal of Contemporary Multidisciplinary Research, 2024)
This study aims to evaluate the supervision strategy implemented by the Head of the Regional Revenue Agency (Bapenda) of Majalengka Regency in improving employee work effectiveness. Supervision in the context of government organizations is very important to ensure that organizational goals can be achieved efficiently and effectively. In this study, we examine various supervision strategies, including surveys, authorized supervision, and other approaches used by the Head of the Agency to improve employee performance. The research method used is qualitative, with data collection through interviews and literature studies. The results of the study indicate that good supervision can improve employee work motivation, service quality, and operational efficiency. In addition, we also identify challenges in implementing supervision strategies and provide recommendations to overcome these obstacles in order to improve employee performance at Bapenda Majalengka Regency